2021
DOI: 10.3802/jgo.2021.32.e53
|View full text |Cite
|
Sign up to set email alerts
|

Major clinical research advances in gynecologic cancer in 2020

Abstract: In 2020 series, we summarized the major clinical research advances in gynecologic oncology with providing representative figures of the most influential study for 1 of each 3 gynecologic cancers: cervix, ovary, and uterine corpus. Review for cervical cancer covered targeted agents and immune checkpoint inhibitors, adjuvant radiation therapy or concurrent/sequential chemoradiation therapy after radical hysterectomy in early cervical cancer, radical surgery in early cervical cancer; and prevention and screening.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
0
15
0
1
Order By: Relevance
“…In addition, there is evidence that patients receiving concurrent chemoradiotherapy had better prognosis and higher OS compared with radiotherapy alone, both in early (62)(63)(64) and advanced (65-67) stages. At the same time, some studies have shown that preoperative or postoperative combination chemoradiotherapy, neoadjuvant chemotherapy or immunotherapy can improve patient progression-free and overall survival (62,63,66,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). Despite these harmful effects, radiotherapy is still an effective treatment for CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that patients receiving concurrent chemoradiotherapy had better prognosis and higher OS compared with radiotherapy alone, both in early (62)(63)(64) and advanced (65-67) stages. At the same time, some studies have shown that preoperative or postoperative combination chemoradiotherapy, neoadjuvant chemotherapy or immunotherapy can improve patient progression-free and overall survival (62,63,66,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). Despite these harmful effects, radiotherapy is still an effective treatment for CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…PARPi has changed the treatment pattern of ovarian cancer. Many clinical trials and real-world studies have confirmed that PARPi can significantly prolong the PFI of patients with ovarian cancer (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The ovarian cancer study reviewed focused on pharmaceuticals and immunological circuit blockers, postoperative radiotherapy or multiple simultaneous chemotherapy, and radiation therapy after laparoscopic procedure in precancerous cervical cancer, severe operation in precancerous cervical cancer, and prophylaxis and monitoring. [ 26 ].…”
Section: Related Workmentioning
confidence: 99%